2021
DOI: 10.3390/microorganisms9030530
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Phenylketonuria (PKU) Gut Microbiome

Abstract: Phenylketonuria (PKU) is an inborn error of phenylalanine metabolism primarily treated through a phenylalanine-restrictive diet that is frequently supplemented with an amino acid formula to maintain proper nutrition. Little is known of the effects of these dietary interventions on the gut microbiome of PKU patients, particularly in adults. In this study, we sequenced the V4 region of the 16S rRNA gene from stool samples collected from adults with PKU (n = 11) and non-PKU controls (n = 21). Gut bacterial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…As the use of arginine and carnitine supplementation was associated with both differences in faecal microbiome as well as laxative use, the observed difference in microbiome composition may be due to collinearity. As reported previously [16] , [23] , [28] , the faecal microbiome of PKU patients differs from that of healthy control subjects. In this study we show for the first time a different faecal microbiome in UCD patients, compared to both PKU and healthy controls.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As the use of arginine and carnitine supplementation was associated with both differences in faecal microbiome as well as laxative use, the observed difference in microbiome composition may be due to collinearity. As reported previously [16] , [23] , [28] , the faecal microbiome of PKU patients differs from that of healthy control subjects. In this study we show for the first time a different faecal microbiome in UCD patients, compared to both PKU and healthy controls.…”
Section: Discussionsupporting
confidence: 61%
“…The increased abundance of Lachnospiracea was also seen in the faecal microbiome of pigs fed with a comparable diet to PKU patients: a low natural protein diet supplemented with amino acids [32] . Two studies with PKU patients reported opposite findings: both reported reduced prevalence of Lachnospiraceae [16] , [28] . In the study of Pinheiro de Oliveira [16] some patients used antibiotics (25% of the PKU group and 30% of the CON group used antibiotics in the 6 months preceding the faecal sample collection) and all patients were children.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, a particularly divergent response in glucose and amino acid metabolism was observed between the affected and control groups. Unlike children with PKU, Mancilla et al (7) reported a significant differences in the abundance of specific bacterial groups in adult PKU patients. But the same was that both adults and children are involved in the abnormality of the glucose metabolism pathway.…”
Section: Introductionmentioning
confidence: 99%
“…( Pinheiro de Oliveira et al, 2016 ; Bassanini et al, 2019 ). Also in adult PKU patients, the gut microbiota, recently investigated by Mancilla et al (2021) , showed a similar pattern with an enrichment in Clostridium and a depletion in Faecalibacterium , but with a less pronounced abundance of Blautia spp.…”
Section: Dietary Treatment In Iems and Gut Microbial Profilementioning
confidence: 69%